An Organic Nanofibrous Polymeric Composite for Ratiometric Detection of Diethyl Chlorophosphate (DCP) in Solution and Vapor. Issue 13 (1st April 2020) - Guria, Uday Narayan; Maiti, Kalipada; Ali, Syed Samim; Gangopadhyay, Ankita; Samanta, Sandip Kumar; Roy, Krittish; Mandal, Dipankar; Mahapatra, Ajit K.
Abstract: Diethyl Chlorophosphate (DCP) is an important nerve agent mimic. Its misused use by terrorists and accidental release from industries creates severe panic among the general public. So, nowadays DCP sensing is of great interest to researchers. Herein, polymeric nanofibers in conjunction with 3‐(benzothiazol)‐5‐bromo‐2‐hydroxybenzaldehyde oxime (BBHO) was prepared as a specific sensing device for nerve gas simulant DCP. Scanning electron microscopic study revealed Abstract : Polymeric nanofibers in conjunction with 3‐(benzothiazol)‐5‐bromo‐2‐hydroxybenzaldehyde oxime (BBHO ) were prepared as a specific ratiometric sensing device for nerve gas simulant DCP. The electrospun nanofiber mat displayed distinct naked eye as well as fluorescence color change upon exposure to gaseous DCP.